Catastrophic flash flood triggered by an extreme rainfall event in el rodeo village, january 2014. Northwestern pampean ranges of Argentina - Esper Angillieri, María Yanina (2017)
Flash floods occur periodically in the hilly areas of Argentina, but since they generally occur at inhabited areas, these are rarely registered. Several factors contribute to the occurrence of flash floods: heavy seasonal rains, rugged topography and geological structures. On Thursday night, 23 January 2014 an extreme rainfall event, took place in El Rodeo, Catamarca Province, triggering an unexpected flash flood. This flood caused 14 fatalities and great economic losses in the main localities of the Ambato Department. Steep slope gradients facilitated the quick drainage of the precipitated volumes. Water, boulders and debris channeled downstream caused severe stream bank erosion and major damage to houses roads and bridges. This paper presents a morphometric analysis in order to determine some geomorphic characteristics of the Ambato River basin, together with a preliminary analysis of the flood hazard potentially damaging to inhabitants and infrastructure to downstream villages. The study was carried out using high-resolution satellite data acquired before and after the event. The drainage networks were derived from Aster GDEM V2 and satellite images.